Immunodominant T-cell epitopes in the factor VIII C2 domain are located within an inhibitory antibody binding site - Pratt, Kathleen P.; Qian, Jiahua; Ellaban, Ekram; Okita, David K.; Diethelm-Okita, Brenda M.; Conti-Fine, Bianca; Scott, David W. (Thrombosis and Haemostasis, 2004)
Formation of inhibitor antibodies to factor VIII (FVIII) is a major complication of FVIII replacement therapy for hemophilia A patients, and it occurs through a T-cell dependent process. The C2 domain of FVIII contains epitopes that are recognized by antibody inhibitors. We have examined regions of the C2 domain that form epitopes for T cells in mice congenitally deficient in FVIII. We obtained CD4+ T cells from mice immunized by intravenous infusion of therapeutic doses of recombinant human FVIII (rFVIII), or by subcutaneous injections of rFVIII or recombinant human C2 domain in adjuvant. In all cases, the T cells recognized most strongly and consistently two overlapping peptides that spanned residues 2191 to 2220 of the C2 domain. Analysis of the crystal structure of human factor VIII C2 bound to a human monoclonal antibody, BO2C11, showed these residues also constitute part of a human alloimmune B-cell epitope (Spiegel et al., Blood 2001; 98: 13-19).This region includes one of the “hydrophobic spike” protrusions, consisting of M2199 and F2200, as well as the basic residues R2215 and R2220. These residues contribute to membrane binding and to association with von Willebrand factor (vWF).These findings suggest that a major T-cell epitope in the C2 domain recognized by hemophilic mice is located within the same region that binds to inhibitors, vWF, and activated membranes.
Keywords: T-cell epitopes; factor VIII; C2 domain